2011
DOI: 10.1007/s00384-011-1302-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SATB1 overexpression with the progression of human rectal cancer

Abstract: Background and aims To date, the association between special AT-rich sequence-binding protein 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
84
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 19 publications
12
84
3
Order By: Relevance
“…The Meng et al and Zhang et al studies observed a correlation of SATB1 protein expression with advanced disease stage and increased tumor depth of invasion [2,4]. However, both the Nodin et al and our study did not show any correlation indicative of a poorer disease outcome of SATB1 expression with patient characteristics [3].…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The Meng et al and Zhang et al studies observed a correlation of SATB1 protein expression with advanced disease stage and increased tumor depth of invasion [2,4]. However, both the Nodin et al and our study did not show any correlation indicative of a poorer disease outcome of SATB1 expression with patient characteristics [3].…”
Section: Discussioncontrasting
confidence: 74%
“…The SATB1 protein expression frequencies in CRC in these reports vary between 42% -59%. In normal colonic mucosa these frequencies varied between 3% -26% [2][3][4]. In our study, we observed a frequency of approximately 18% in cancerous tissues and a relatively high frequency of 52% in normal tissues.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations